(untitled) (CIPEEX, 2022)
THE ACQUIRED IMMUNODEFICIENCY SYNDROME (AIDS/AIDS) HAS THE HUMAN IMMUNODEFICIENCY VIRUS (HIV) AS ITS ETIOLOGICAL AGENT, IT BELONGS TO THE RETROVIRIDAE FAMILY AND THE LENTIVIRUS GENERA. THIS VIRUS HAS TROPISM FOR CD4+ T HELPER LYMPHOCYTES (L TCD4+), CAUSES THE DEATH OF THESE CELLS AND LEAVES THE BODY SUSCEPTIBLE TO OPPORTUNISTIC INFECTIONS, LEADING TO DEATH. IN ORDER TO SUPPRESS THE VIRAL LOAD AND REDUCE THE MORBIDITY AND MORTALITY OF INFECTED PEOPLE, ANTIRETROVIRAL THERAPY (ART) HAS BEEN WIDELY USED AND ADAPTED. IN FEBRUARY 2017, THE MINISTRY OF HEALTH UPDATED THE PREFERENTIAL TREATMENT REGIMEN FOR ADULTS WITH HIV/AIDS, REPLACING EFAVIRENZ (EFV) FROM THE OLD REGIMEN WITH DOLUTEGRAVIR (DTG). THUS, CURRENTLY THE PREFERRED REGIMEN FOR ADULTS IS COMPOSED OF LAMIVUDINE (3TC) + TENOFOVIR (TDF) + DOLUTEGRAVIR (DTG). DTG IS AN INHIBITOR OF THE HIV CYCLE INTEGRASE ENZYME, THIS DRUG HAS HIGH POTENCY, HIGH GENETIC BARRIER, THAT IS, HIGH POTENTIAL FOR DURABILITY TO THE RESISTANCE OF THIS NEW REGIMEN AND ALSO HAS FEW ADVERSE EVENTS. DESPITE THE HIGH EFFICACY OF ART, NON-ADHERENCE INCREASES THE POSSIBILITY OF DEVELOPING RESISTANT VIRAL STRAINS, REDUCING THERAPEUTIC OPTIONS. IN THIS CONTEXT, THE OBJECTIVE OF THIS STUDY WAS TO EVALUATE ADHERENCE TO THE NEW ART REGIMEN IN HIV/AIDS PATIENTS IN THE CITY OF ANÁPOLIS/GO. THIS IS A CROSS-SECTIONAL DESCRIPTIVE STUDY, DEVELOPED AT THE DR. ILION FLEURY JR. HEALTH UNIT, A REFERENCE IN DIAGNOSIS AND TREATMENT OF STIS/AIDS IN THE CITY OF ANÁPOLIS/GO. THE €ŒCUESTIONARIO PARA LA EVALUACIÓN DE LA ADHESIÓN AL TRATAMIENTO ANTIRRETROVIRAL - CEAT-VIH€ WAS USED TO ASSESS ADHERENCE TO ART. PATIENTS’ CHARTS WERE ANALYZED TO OBTAIN LABORATORY RESULTS. DATA WAS ANALYZED USING THE SPSS STATISTICS PROGRAM. STUDY APPROVED BY THE CEP OF THE EVANGELICAL UNIVERSITY OF GOIS. (REGISTERED UNDER NO. 1,676,182). EIGHTY-EIGHT 88 HIV/AIDS PATIENTS (65 MEN/23 WOMEN) AGED 18-67 YEARS WERE INCLUDED IN THE STUDY. ALTHOUGH THERE ARE DIFFERENT FORMS OF TRANSMISSION OF THE VIRUS, SUCH AS SHARING SYRINGES AND SHARP OBJECTS, BLOOD TRANSFUSIONS, AND FROM MOTHER TO CHILD (PREGNANCY, CHILDBIRTH, BREASTFEEDING), THE MAIN FORM OF CONTAGION ACCOUNTED FOR WAS SEXUAL (97%). AMONG THE 88 PATIENTS INCLUDED IN THE STUDY, THERE ARE TWO GROUPS, (1) PATIENTS WHO WERE USING THE PREFERRED ART TREATMENT REGIMEN (TENOFOVIR (TDF) + LAMIDUVINE (3TC) + DOLUTEGRAVIR (DTG) - THIS GROUP CONSISTED OF 72 PATIENTS; AND (2) PATIENTS WHO HAVE DOLUTEGRAVIR (DTG) IN THEIR TREATMENT REGIMEN, WITH A TOTAL OF 16 PATIENTS IN THIS GROUP. MOST PATIENTS HAD ADHERENCE CLASSIFIED AS STRICT OR GOOD (81%), WHICH COULD BE CONFIRMED BY LABORATORY RESULTS, SINCE 87.5% OF PATIENTS HAD UNDETECTABLE VL. IN ADDITION, THE HIGH RATE OF ADHERENCE CORRELATED WITH THE LOW LEVELS OF ADVERSE EVENTS REPORTED BY PATIENTS. ONLY 3% OF PATIENTS WERE CLASSIFIED AS HAVING LOW ADHERENCE BY CEAT-HIV, ALTHOUGH 12.5% €‹€‹HAD DETECTABLE VL, CHARACTERIZING LABORATORIAL LACK OF ADHERENCE TO ART, THESE PATIENTS WERE MOSTLY MALE. IT IS ESSENTIAL TO CONTINUE THE MONITORING OF NON-ADHERENCE RATES, AS WELL AS TO ASSESS THE DIFFICULTIES THAT LEAD PATIENTS TO DROP OUT OF TREATMENT,AND THUS SUBSIDIZE SPECIFIC ACTIONS AIMED AT FACING THIS PROBLEM IN THE MOST VULNERABLE GROUPS. THE EVALUATION OF A GREATER NUMBER OF PATIENTS IN MULTIPLE REFERENCE UNITS FOR THE TREATMENT OF HIV/AIDS INFECTION IN BRAZIL AND THE APPLICATION OF DIRECT AND INDIRECT METHODS TO ASSESS ADHERENCE TO ART IS CRUCIAL TO FIND THE VARIABLES MOST ASSOCIATED WITH LOW ADHERENCE. DATA FROM THE ASSESSMENT OF ADHERENCE TO THE NEW DTG-CONTAINING REGIMEN INDICATE A HIGH RATE OF GOOD ADHERENCE TO ART, VIRAL LOAD CONTROL, AND A LOW LEVEL OF MEDICATION-ASSOCIATED ADVERSE EFFECTS.